SOME REFLECTIONS ON TYPICAL MOTIFS IN FOLK EPICS (Web of Teachers: Inderscience Research, 2025)
The article discusses the features of the description of the plot system of traditional common typical places characteristic of folk epics. In particular, the ideological and artistic content of the traditional work of the folk epic, the tradition of epic images of the inner types of the epic, their similarity, similarity and difference in the image of the heroic, romantic and historical epic. the identification of which can be determined by comparing the pictorial means directly covered by the plot of typical places is revealed through the analysis of sources.